New pathways in the gold-catalyzed cycloisomerization of furanynes - Hashmi, A. Stephen K. (Pure and applied chemistry, 2010)
The most familiar gold-catalyzed cyclization pathway for furanyne substrates leads to synthesis of phenols, but new reaction pathways have recently been discovered. The mechanistic background and the synthetic possibilities of these alternative pathways leading to new heterocyclic products are discussed.
Gesehen am 29.09.2022